Nuovi dati di cattura di Anophthalmus manhartensis fuartensis Colla e discussione della sua validita sottospecifica (Coleoptera: Carabidae: Trechinae) - Bognolo, Marco (Acta entomologica slovenica (Ljubljana), 1999)
New data on the distribution of Anophthalmus manhartensis fuartensis Colla are presented. The validity of this subspecies of A. manhartensis Meschnigg is debated, with comparision in some features of each population (shape of elytra, pronotum and copulatory piece).
Keywords: entomologija; hrošči; Italija; Italy; Slovenia; Slovenija; zoogeografija; zoologija; zoology